Design and Implementation of an Android-Based Student Attendance Application Utilizing QR Codes to Enhance Presence Efficiency - Dyah Ayu Nurmumpuni; Angelina Hadriani (INKOFAR, 2026)
Background Manual student attendance recording in educational institutions is inefficient, error prone, and susceptible to proxy attendance (titip absen). Physical presence recapitulation also delays real time attendance reporting for administrators and parents. Purpose This study designs, implements, and evaluates an Android based attendance information system incorporating dual factor verification through dynamic QR codes and location based geofencing. Methodology The system combines dynamically rotating QR tokens (60 second expiration) with the Haversine formula for real time GPS distance validation within a 50M radius boundary. System performance and user acceptance were evaluated using Black box testing, UAT, MOS surveys (N = 5 teachers, N = 30 students), response latency benchmarking, and server load stress testing up to 100 concurrent requests. Findings Empirical evaluation demonstrates that the proposed system reduces classroom attendance duration from an average of 12.5 minutes (10 to 15 minutes) to 1.4 minutes per class session, achieving an 88.8% reduction in administrative time. The average MOS satisfaction score reached 4.57/5.00 for teachers and 4.62/5.00 for students (Excellent category). Response latency benchmarks yielded an average response time of 245 ms under standard operational conditions, maintaining a 0.0% error under load tests up to 50 concurrent requests. Implications The solution offers primary educational institutions a cost effective attendance verification without requiring dedicated door terminal hardware, while providing guidelines for managing indoor GPS signal drift. Originality The primary scientific contribution lies in integrating short lived cryptographic QR tokens with GPS geofencing on commodity mobile devices, providing a zero hardware, zero proxy presence verification mechanism tailored for primary schools.